Adult Height in Girls With Idiopathic Premature Adrenarche: A Cohort Study and Design of a Predictive Model - Mejorado-Molano, Francisco Javier; Sanz-Calvo, María Luisa; Posada-Ayala, Ana; Caballo-Roig, Nieves; Gavela-Pérez, Teresa; Mahillo-Fernández, Ignacio; Soriano-Guillén, Leandro (Frontiers in Endocrinology, 2022)
Introduction Idiopathic premature adrenarche (IPA) is considered a normal variant of puberty, presenting more commonly in females. There are concerns as to whether IPA alters the final height of these girls. Our main objectives were to a) compare the adult height of girls with IPA against their target height and b) design a mathematical model to predict adult height at diagnosis in females with IPA. Materials and Methods A cohort study of girls with IPA was conducted from the time of IPA diagnosis until adult height. The following data were collected: target height; perinatal history; anthropometric and biochemical variables and bone age at diagnosis; age at Tanner stage 2 and menarcheal age; and adult height. First, we performed a univariate statistical analysis after which we carried out a multiple linear regression analysis using adult height as the dependent variable. Results We obtained data from 79 females diagnosed with IPA with a mean adult height of 164.6 cm (95% CI: 163.36–165.85 cm). The mean follow-up time was 6.60 years. Average age at Tanner stage 2 was 9.71 years. Mean menarcheal age was 11.64 years. There were no significant differences between target height and adult height. Of the several predictive models designed for these patients, one of them, which included bone age, obtained an R2 value of 71%. Conclusions Although slightly advanced puberty was observed among the girls with IPA, their adult height was preserved. The use of predictive models of adult height on diagnosis of IPA could facilitate closer follow-up of girls at risk of reduced adult height.